Optimization of the Biopellet Manufacturing Process: Effect of Adhesive Concentration with Recycled Coffee Grounds and Cocopeat on Biopellet Properties - Nurjannah, Ika; Sari, Handini Novita (Proceedings of the International Conference on Green Technology; Vol 14 No 1 (2024): Proceeding of 14th International Conference on Green Technology, 2024)
Biopellets are an environmentally friendly organic waste management solution. The use of biopellets can help reduce negative impacts on the environment and create a cleaner and healthier environment. In this study, coffee grounds and cocopeat waste were used as the main raw materials for the biopellet making process with a ratio of 1:1, The quality testing of biopellets includes ash content, calorific value, moisture content, and combustion rate due to the effect of tapioca flour adhesiv concentration with variations in composition of 10%, 15%, and 20%. The results of this study show that the concentration of tapioca flour adhesives has a significant impact on the quality of biopellets. The adhesive's concentration increases with moisture and ash content, while decreasing its calorific value. Biopellets with an adhesive concentration of 10% have the lowest moisture content and ash content values of 5.76% and 2.02% and the highest calorific value of 4842.33 Cal/gr with a combustion rate of 2.0 gr/min. Overall, biopellets that meet the SNI 8675:2018 standard are biopellets with adhesive concentrations of 10% and 15%, while biopellets with adhesive concentrations of 20% have not met because the calorific value is still less than 4000 Cal/gr.